Role of diagnostic hysteroscopy in evaluating patients with abnormal uterine bleeding in a tertiary care centre - Mohite, Apeksha M.; Kapote, Deepali S.; Fonseca, Michelle (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Abnormal uterine bleeding is one of the commonest conditions amongst patients attending gynaecology OPD which also leads to significant disruption in a normal lifestyle. The causes of abnormal uterine bleeding are heterogeneous and complex. A systematic evaluation with detailed history and physical examination is foremost important in reaching diagnosis. Hysteroscopy is not only safe, quick and observes entire uterine cavity but also helps in precision in sampling and increases accuracy of diagnosis. It is also curative in conditions such as polyps, fibroids, uterine synechiae, menorrhagia and lost intrauterine contraceptive device. The aim of the study is to evaluate the role of hysteroscopy as a screening method in patients with AUB & compare to their USG findings and to the histopathological reports of the endometrial biopsy. Methods: This is a prospective observational study conducted at a tertiary healthcare centre over a period of 18 months, in 50 females belonging to pre, peri and post-menopausal age group. Sampling was done based on selection criteria after obtaining valid consent from the study group. Results: Hysteroscopy has a definitive role in evaluation of patients presenting with abnormal uterine bleeding with high sensitivity, specificity, PPV and NPV with immediate results. Conclusions: The above study concludes that the accuracy of diagnosing the cause of abnormal uterine bleeding is more with hysteroscopy followed by D and C then USG combined with D and C.